2016
DOI: 10.3390/s16050617
|View full text |Cite
|
Sign up to set email alerts
|

Photon Counting Imaging with an Electron-Bombarded Pixel Image Sensor

Abstract: Electron-bombarded pixel image sensors, where a single photoelectron is accelerated directly into a CCD or CMOS sensor, allow wide-field imaging at extremely low light levels as they are sensitive enough to detect single photons. This technology allows the detection of up to hundreds or thousands of photon events per frame, depending on the sensor size, and photon event centroiding can be employed to recover resolution lost in the detection process. Unlike photon events from electron-multiplying sensors, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Thus, well over 1,000 electron-hole pairs are created by a single photon, which are further amplified in the diode, see Figure 7. One advantage of this technology is that the single gain step produces a narrow pulse height distribution [115,116], which can be used to detect photon numbers. From the timing point of view, this single gain step results in low transit time spread and therefore low timing jitter [117].…”
Section: Hybrid Detectorsmentioning
confidence: 99%
“…Thus, well over 1,000 electron-hole pairs are created by a single photon, which are further amplified in the diode, see Figure 7. One advantage of this technology is that the single gain step produces a narrow pulse height distribution [115,116], which can be used to detect photon numbers. From the timing point of view, this single gain step results in low transit time spread and therefore low timing jitter [117].…”
Section: Hybrid Detectorsmentioning
confidence: 99%
“…Single photon detection is also possible with electron-bombarded (EB) sensors, where the photoelectrons from the photocathode are accelerated directly into a CCD or CMOS sensor [62], [63], [64], [65], [66]. Unlike MCPs where the statistical electron multiplication process creates a broad pulse height distribution, in EB sensors the photon event brightness depends on the gain voltage.…”
Section: Wide-field Time-correlated Single Photon Counting Imaging Tementioning
confidence: 99%
“…The key issue of MAPS radiation detection is to study its response characteristics to rays or particles. Experiments have confirmed that MAPS is sensitive to single ionized particles and generates radiation-responsive events in pixel arrays [ 7 , 8 ]. Different particles, such as X-rays, γ photons, and α and β particles, show its specific size and shape of typical response events in a frame [ 9 ].…”
Section: Introductionmentioning
confidence: 99%